Palladium‐Catalyzed Distal C−H Selenylation of 2‐Aryl Acetamides with Diselenides and Selenyl Chlorides. Issue 24 (9th November 2020) - He, Meicui; Gu, Linghui; Tan, Yuqiang; Wang, Yang; Wang, Yuchi; Zhang, Chunran; Ma, Wenbo
Abstract: A convenient and effective method of palladium‐catalyzed C−H selenylation of the 2‐aryl acetamides assisted with removable 8‐aminoquinoline with readily available diselenides and selenyl chlorides has been developed. This selenylation reaction is scalable and tolerates a wide range of functional groups, providing a straightforward way of the preparing unsymmetrical diaryl selenides and dibenzoselene‐pinone. Preliminary mechanistic studies indicated that a single‐electron transfer type mechanism and facile C−H metalation are operative. Abstract :